Lisbon Urban Heat Island Updated: new Highlights about the Relationships between Thermal Patterns and Wind Regimes - Lopes, António (2017)
Urban growth implies significant modifications in the urban climate. To understand the influence of the city of Lisbon on the urban boundary layer, a mesoscalemeteorological network was installed in 2004. The main goals of the present study are to update the results of the research published in 2007 and to bring more precise information about the relationship between the Urban Heat Island (UHI) and the regional and local wind systems. The highest frequencies of the UHI were found in the city centre (Restauradores). In the green park ofMonsanto, the highest frequency occurred between −2 and0∘C.During the summer, the effect of the breezes was observed in Bel´em, lowering the temperature.The“strong” UHI (intensity >4∘C) occurredmore often during the summer, with median values of 2∘C by night and 1.8∘C by day.The highest frequencies of UHI occurred for winds between 2 and 6m/s and were not associated with atmospheric calm, as pointed out in the literature.Winds above 8m/s inhibit the occurrence of strong UHI in Lisbon. Summer nighttime strong UHI should be further investigated, due to the heat stress consequences on the population and probable increase of energy consumption.